2017
DOI: 10.1021/acsami.6b16860
|View full text |Cite
|
Sign up to set email alerts
|

Boron-Enhanced Growth of Micron-Scale Carbon-Based Nanowalls: A Route toward High Rates of Electrochemical Biosensing

Abstract: In this study, we have demonstrated the fabrication of novel materials called boron-doped carbon nanowalls (B:CNWs), which are characterized by remarkable electrochemical properties such as high standard rate constant (k°), low peak-to-peak separation value (ΔE) for the oxidation and reduction processes of the [Fe(CN)] redox system, and low surface resistivity. The B:CNW samples were deposited by the microwave plasma-assisted chemical vapor deposition (CVD) using a gas mixture of H/CH/BH and N. Growth results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 70 publications
1
42
0
Order By: Relevance
“…Boron incorporation into the carbon lattice slightly positively affects nanowall length, which is not directly translated into an enhancement of the electrical conductivity; however, the latter, jointly with the optical bandgap, depends on the [B]/[C] ratio (Figure 6b). Overall, the incorporation of boron into the CNW lattice structure induces the unique effect of enhanced electrochemical performance and improved charge transfer [42,43].…”
Section: Resultsmentioning
confidence: 99%
“…Boron incorporation into the carbon lattice slightly positively affects nanowall length, which is not directly translated into an enhancement of the electrical conductivity; however, the latter, jointly with the optical bandgap, depends on the [B]/[C] ratio (Figure 6b). Overall, the incorporation of boron into the CNW lattice structure induces the unique effect of enhanced electrochemical performance and improved charge transfer [42,43].…”
Section: Resultsmentioning
confidence: 99%
“…Fitting of the high resolution B1s spectrum indicates the presence of different forms of C‐B bands (Figure 1d‐ii). From the fitting of the high resolution C1s spectrum, we found that the B‐CNW coating exhibited a C‐B band at a peak position of 282.3 eV [ 15 ] (Figure 1d‐iii), which contributed to about 1% of the carbon bonding. The comparison of the high‐resolution C1s spectra obtained from the bare CFs and the B‐CNW CFs with different deposition times is summarized in Figure S4, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…For example, an electrode described as Si/B-NCD-2k has a (B)/(C) ratio of 2000 ppm. The synthesis of carbon layers (BDD, CNW, and B-NCD) on the silicon/quartz glass surface, along with the selection of deposition parameters, was carried out in accordance with the procedures described in earlier works [ 18 , 25 , 31 , 33 , 69 ] by the team of Prof. Robert Bogdanowicz from the Department of Metrology and Optoelectronics from the Faculty of Electronics, Telecommunications and Informatics of the Gdańsk University of Technology.…”
Section: Methodsmentioning
confidence: 99%
“…Intensive research on carbon nanotubes contributed to the discovery of the so-called carbon nanowalls (CNWs), which are a system of graphite walls set vertically to the substrate [ 32 ]. Carbon nanowalls are variously branched networks with a morphological structure resembling a labyrinth [ 33 , 34 , 35 , 36 ]. The basic properties of carbon nanowalls, which are of fundamental importance for their potential applications, are primarily the interesting structure of the material, i.e., sharp edges or a high surface-to-volume ratio, which makes it an ideal functional support for synthesizing a new composite material with a large area.…”
Section: Introductionmentioning
confidence: 99%